Exploring salient dimensions in a free sorting task: A cross-country study within the elderly population. (September 2017) - Cliceri, Danny; Dinnella, Caterina; Depezay, Laurence; Morizet, David; Giboreau, Agnés; Appleton, Katherine M.; Hartwell, Heather; Monteleone, Erminio
Highlights: Free sorting task was applied on different age groups of elderly population. Salient dimensions in the process of food categorization were considered. Free sorting task resulted a suitable and reliable method to use with older adults. Familiarity was the main factor that affected the categorization of food products. Categorization maps can be potentially used to obtain reliable information of sensory dimension. Abstract: Free sorting tasks have been widely applied on different age segments to study the categorization of foods. However the method has received little attention in the investigation of older adults' perception. Given the importance of understanding elderly perceptions in order to develop acceptable products, the main objective of this study was to investigate the factors that were able to affect the categorization of samples within different age segments of the healthy elderly consumers. Furthermore, in order to support the obtained configurations, the applicability of a free sorting task within different age segments of elderly population was investigated. The role of familiarity was considered to better understand the process of food categorization. A free sorting and a liking task were applied on French and Italian elderly to study perception and preference of familiar (peas) and less familiar (sweetcorn) vegetables. Similarities between the categorization maps, the preference maps and the sensory maps from vegetable samples were assessed through the RV coefficient and map visual inspection. Familiarity with the product was the main factor affecting the categorization among elderly. Categorization maps from a familiar vegetable were found to be suitable to obtain information on sensory and hedonic dimensions, while maps obtained from a less familiar vegetable mainly depicted sensory variability. The free sorting task was found to be a suitable method to use with healthy older adults, that allowed the detection of differences in the categorization of stimuli even among the more aged representatives of the elderly population.